Enhanced axon outgrowth and improved long‐distance axon regeneration in sprouty2 deficient mice. Issue 3 (14th August 2014) - Marvaldi, Letizia; Thongrong, Sitthisak; Kozłowska, Anna; Irschick, Regina; Pritz, Christian O.; Bäumer, Bastian; Ronchi, Giulia; Geuna, Stefano; Hausott, Barbara; Klimaschewski, Lars
ABSTRACT Sprouty (Spry) proteins are negative feedback inhibitors of receptor tyrosine kinase signaling. Downregulation of Spry2 has been demonstrated to promote elongative axon growth of cultured peripheral and central neurons. Here, we analyzed Spry2 global knockout mice with respect to axon outgrowth in vitro and peripheral axon regeneration in vivo. Neurons dissociated from adult Spry2 deficient sensory ganglia revealed stronger extracellular signal‐regulated kinase activation and enhanced axon outgrowth. Prominent axon elongation was observed in heterozygous Spry2+/− neuron cultures, whereas homozygous Spry2−/− neurons predominantly exhibited a branching phenotype. Following sciatic nerve crush, Spry2+/− mice recovered faster in motor but not sensory testing paradigms (Spry2−/− mice did not tolerate anesthesia required for nerve surgery). We attribute the improvement in the rotarod test to higher numbers of myelinated fibers in the regenerating sciatic nerve, higher densities of motor endplates in hind limb muscles and increased levels of GAP‐43 mRNA, a downstream target of extracellular regulated kinase signaling. Conversely, homozygous Spry2−/− mice revealed enhanced mechanosensory function (von Frey's test) that was accompanied by an increased innervation of the epidermis, elevated numbers of nonmyelinated axons and more IB4‐positive neurons in dorsal root ganglia. The present results corroborate the functional significance of receptor tyrosine kinase signaling inhibitors for axon outgrowth during development and nerve regeneration and propose Spry2 as a novel potential target for pharmacological inhibition to accelerate long‐distance axon regeneration in injured peripheral nerves. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 217–231, 2015